The Role of Hidayatullah Mosque Youth in Maximizing the Function of Nurul Iman Prayer Room During the Pandemic in Lengki Hamlet, Prayungan Village, Lengkong Subdistrict - Arifin, Zainal; Fauzi, Muhamad Umar; Firmansyah , Delly; Mahmudin , Mahmudin; Ningsih , Rumiati (STAI Miftahul ULa Nganjuk, 2023)
This research explores the role of the youth at Masjid Hidayatullah in Dusun Lengki, Desa Prayungan, Kec. Lengkong, in sustaining the function of Mushola Nurul Iman during the COVID-19 pandemic. The study focuses on how the youth adapted to the challenges imposed by the pandemic, including restrictions on physical gatherings, and how they innovatively used technology to maintain religious and social activities. By employing the Participatory Action Research (PAR) method, this research highlights the involvement of youth in organizing online religious events, providing community support through social welfare programs, and fostering intergenerational cooperation. The findings indicate that the youth played a critical role in ensuring the continuity of mosque activities, demonstrating leadership, adaptability, and social responsibility. Furthermore, their active engagement contributed to both their personal development and the overall resilience of the community. This study emphasizes the importance of empowering mosque youth, as their involvement has long-term benefits for both community cohesion and individual growth